Faire connivence : l’invention électrique sur scène (1859-1908) - Pauline Picot (Itinéraires)
French theater, which crystallizes a collective imaginary of fluids prevalent in the 19th century, sometimes acts as a relay for—or even manufactures—scientific inventions that may seem fanciful to the contemporary mind. Barrière and Sardou’s “electro-medical chains”, Georges Feydeau’s “ecstatic armchair” or André de Lorde’s “electrifying spike” are some of the devices put on stage to accentuate the blurring between scientific reality and theatrical illusion in a period brimming/overflowing with discoveries. These inventions also bring up issues of the moment (the bourgeois quest for pleasure, relations between the sexes and the excesses of modernity), while also revealing the changing face of science in the second half of the century.